Efforts of implementing ultra‐flexible thin‐film encapsulation for optoelectronic devices based on atomic layer deposition technology - Guanran Wang; Yu Duan (SmartMat)
Abstract Flexible, wearable electronics are the future of electronics. Although organic photovoltaic devices have the advantages of high efficiency, low cost, and flexibility, they face the problem of failure due to the effects of water vapor in the environment. Therefore, the development of encapsulation films with outstanding mechanical and encapsulation properties is the key to realizing wearable devices. This review provides an overview of the development of thin‐film encapsulation (TFE), the application of TFE in the field of optoelectronics, recent advances in the field of flexible encapsulation with TFE using atomic layer deposition technology, and an outlook on future trends in the field of flexible encapsulation with TFE using atomic layer deposition technology.